Miasis Furuncular Produced by Dermatobia hominis (Diptera: Oestridae) Larvae in Humans: A Report of Three Cases - Elena Moissant de Román; Jessica Quijada; María Elena García; David Simoes; Nynlhe Katiuska Hermoso (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Three human furunculoid myasis cases caused by the Dermatobia hominis's fly larvae, that occurred in Aragua and Guárico States are described. They were: a.- A 35-year-old female who presented a furunculous nodule lesion on her right gluteus region, after visiting the Aragua coast. b.- A 3-year-old child who presented a nodule lesion on the right parietal region, after  haematophagal Diptera punctures. c.- A 7-year-old child who presented furunculous nodule lesion on his right forearm, after several haematophagal Diptera punctures in Guárico State. Common clinical signs of the cases were: intense local itching, inflammation and cutaneous furuncules. The D. hominis' larvae were between 12 and 27 mm in length in all three patients, They were recovered by hand pressure, mechanical extraction or surgically.